Unveiling the Interplay of Institutional Quality, Foreign Direct Investment, Inflation and Domestic Investment on Economic Growth: Empirical Evidence for Latin America - Husnain, Muhammad Ali; Guo, Ping; Pan, Guoqin; Manjang, Matarr (International Journal of Economics and Financial Issues, 2024)
Uplifting economic growth is crucial for the sustained development and prosperity of an economy. The main objective of this study is to investigate the impact of institutional quality, foreign direct investment (FDI), inflation, and domestic investment on the economic growth of Latin America from 1996 to 2021. The study utilizes a combination of panel unit root testing, cross-sectional dependency testing, panel cointegration testing, and the Panel Autoregressive Distributive Lag (PARDL) technique to shed light on the dynamics of the region’s economic development. The panel cointegration techniques confirm the existence of a long-run relationship among the selected variables over the chosen time frame. The PARDL technique is employed to determine the short- and long-run impact of institutional quality, FDI, inflation, and local investment on the economic growth of Latin America. The results show that institutional quality, FDI, and local investment have a significant positive impact on the economic growth of Latin America, while inflation has a negative impact. These findings suggest that policymakers in Latin America should prioritize improving institutional quality, encouraging FDI, and promoting local investment while controlling inflation. A comprehensive economic strategy that considers both short- and long-term dynamics is necessary, highlighting the importance of an integrated approach that recognizes their interaction. The study recommends improving the quality of institutions, especially political stability, to attract FDI and encourage domestic investment by promoting a business-friendly environment, guaranteeing financial accessibility, encouraging innovations, promoting regional and global integration, controlling inflation, reducing income inequality, and raising the standard of living.